Creative Strategy for Local Content at Radio Republik Indonesia Program 1 Yogyakarta to Serve Local Listeners in 2023 - Fauziah, Elza Nur; Mulawarman, Krisna (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Radio Republik Indonesia in its regional scope has an important role in packaging broadcast programs according to regional needs without violating central RRI rules. Therefore, what are the opportunities for the creative team to provide local content in programs determined by the center? The purpose of this research is to find out the steps of Radio Republik Indonesia Programa 1 Yogyakarta's local content creative strategy to serve local listeners in 2023. This research uses qualitative methods with data collection techniques through interviews, documentation, data reduction, data presentation, and conclusion drawing. The results of this research are: 1). RRI Pro 1 Yogyakarta conducts creative strategies by discussing materials or scripts and brainstorming by following trending topics. 2). Event planning by preparing broadcast needs and song selection. 3). Implementation of the event 4). This research is expected to increase innovations, for example in terms of broadcast content in local content and also more exploratory broadcast styles so that listeners are not bored when listening to the program.